2008
DOI: 10.1097/rhu.0b013e3181826d5b
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Involvement in Systemic Lupus Erythematosus

Abstract: FIGURE 1. Acute arthritis in the right knee of the patient. Significant swelling of the right knee also involved the quadriceps area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
1
1
Order By: Relevance
“…42 These study results may explain the findings in our study and provide crucial clues for elucidating the pathogenesis of epiglottitis from an immunologic perspective. Nevertheless, our results do not appear to be completely consistent with those of prior studies, 9,10 which were mainly case reports or series, because we did not observe significant association between epiglottitis and RA or SLE, possibly due to the ethnic differences and the lack of statistical power. In addition, studies have reported laryngeal involvement in patients with dermatopolymyositis, Behcet disease, systemic sclerosis, and myasthenia gravis.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…42 These study results may explain the findings in our study and provide crucial clues for elucidating the pathogenesis of epiglottitis from an immunologic perspective. Nevertheless, our results do not appear to be completely consistent with those of prior studies, 9,10 which were mainly case reports or series, because we did not observe significant association between epiglottitis and RA or SLE, possibly due to the ethnic differences and the lack of statistical power. In addition, studies have reported laryngeal involvement in patients with dermatopolymyositis, Behcet disease, systemic sclerosis, and myasthenia gravis.…”
Section: Discussioncontrasting
confidence: 99%
“…5,7,8 Moreover, mucosa ulcer and edema of epiglottic structures, cricoarytenoid arthritis, and necrotizing vasculitis have been reported in noninfectious epiglottitis caused by autoimmune disease with laryngeal involvement. [9][10][11] Studies have highlighted the high prevalence of supraglottic involvement in patients with Sjo ¨gren syndrome (SS), Behcet disease, rheumatoid arthritis (RA), and systemic lupus erythematosus (SLE), 10,[12][13][14][15][16] and case reports have indicated that epiglottitis might present as the initial or flare manifestation of SLE. 11,17 Although the aforementioned studies have discovered crucial connections between the 2 rare disease entities, the lack of a control group and small samples have limited the research.…”
Section: Introductionmentioning
confidence: 99%